1996
DOI: 10.2307/1592275
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Antibody Responses to Vaccines and Divergent Body Weights of Chicken Lines Selected for High and Low Humoral Responsiveness to Sheep Red Blood Cells

Abstract: Primary and secondary antibody responses to intramuscularly administered proteins of Eschericia coli (F11), Newcastle disease virus (NCD), infectious bronchitis virus (IB), and infectious bursal disease virus (IBD), respectively, were measured at weekly intervals in two chicken lines. The latter had been divergently selected for high and low antibody responses to sheep red blood cells (SRBC), and in a random-bred control line. An oil-based adjuvant was required to induce primary and secondary antibody response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…Studies directed to broilers or immune (LPS, HuSA) challenge. It has to be kept in (Miller et al, 1992) or layers (Parmentier et al, 1996; mind, however, that levels of 5-HT and CORT in the Siegel et al, 1982) also suggested that higher body blood were measured at one moment: 6 weeks of age, weight (gain) of broilers and layers negatively affected indicating a status, whereas the immune parameters their humoral immune response, whereas enhanced and BWG exemplified responsiveness of the birds. In egg production had less negative impact to the bird's this study, birds were housed in pens with temperatures humoral immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies directed to broilers or immune (LPS, HuSA) challenge. It has to be kept in (Miller et al, 1992) or layers (Parmentier et al, 1996; mind, however, that levels of 5-HT and CORT in the Siegel et al, 1982) also suggested that higher body blood were measured at one moment: 6 weeks of age, weight (gain) of broilers and layers negatively affected indicating a status, whereas the immune parameters their humoral immune response, whereas enhanced and BWG exemplified responsiveness of the birds. In egg production had less negative impact to the bird's this study, birds were housed in pens with temperatures humoral immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Also other non-comparative studies in broilers (Parmentier et al, 2008) and (selected) layer lines suggested that breeding towards a higher body weight (gain) of broilers negatively affected the humoral immune response while the genetic changes of layers towards egg production had less negative impact on the birds immune system. A higher body weight (gain) in layer lines was also related with lower immune competence (Parmentier et al, 1996;Siegel and Gross, 1980;Siegel et al, 1982). A dysfunction of the broiler's specific cellular and humoral immune system has been proposed to underlie the health problems and enhanced disease sensitivity after pressure on the immune system (Miller et al, 1992;Koenen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although testosterone may influence humoral and cell-mediated immune responses (Chen et al 2009), it may not be a relevant explanation in broiler chickens (Shore et al 1993). However, growth rate differences have been correlated with antibody response (Dunnington et al 1993;Parmentier et al 1996). It seems that the higher growth rate of male chickens comes, at least partially, at the cost of their humoral immune response.…”
Section: Immune Responsementioning
confidence: 99%
“…No distinction was made between males and females in the Dutch experiment whereas a difference of Ab titre exists: females have a higher Ab titre against SRBC than males [20] therefore, the trend in Figure 1 was an average over sexes.…”
Section: Discussionmentioning
confidence: 94%